Liposomes as a model for the biological membrane : studies on daunorubicin bilayer interaction - Matos, C. (2012)
In this study the interaction of the antitumoral drug daunorubicin with egg phosphatidylcholine (EPC) liposomes, used as a cell membrane model, was quantified by determination of the partition coefficient (Kp). The liposome/aqueous-phase Kp of daunorubicin was determined by derivative spectrophotometry and measurement of the zeta-potential. Mathematical models were used to fit the experimental data, enabling determination of Kp. In the partition of daunorubicin within the membrane both superficial electrostatic and inner hydrophobic interactions seem to be involved. The results are affected by the two types of interaction since spectrophotometry measures mainly hydrophobic interactions, while zeta-potential is affected by both interpenetration of amphiphilic charged molecules in the bilayer and superficial electrostatic interaction. Moreover, the degree of the partition of daunorubicin with the membrane changes with the drug concentration, due mainly to saturation factors. Derivative spectrophotometry and zeta-potential variation results, together with the broad range of concentrations studied, revealed the different types of interactions involved. The mathematical formalism applied also allowed quantification of the number of lipid molecules associated with one drug molecule.